Reporting Uncertainty and Assessment of Risk: Replication and Extension in a Canadian Setting - Abdel-Khalik, A. Rashad; Graul, Paul R.; Newton, James D. (Journal of Accounting Research, 1986)
Auditing, Subject-to opinion, Canada, Risk assessment